Патоморфологічна характеристика біомінералізації при раку передміхурової залози - Піддубний, А. М.; Поддубный, А. М.; Piddubnyi, A. M. (Запорізький державний медичний університет, 2020)
Дисертаційна робота присвячена актуальній проблемі – оптимізації діагностики та оцінюванню перебігу раку передміхурової залози на тлі процесів біомінералізації. За результатами дослідження установлено клініко-епідеміологічні особливості раку передміхурової залози в Сумській області. Був продемонстрований вплив простатолітів на підвищення експресії Вах (p < 0,001) та Casp3 (p < 0,001), встановлено їх вплив на зміни в кількісному складі запального пухлинного мікрооточення, що виявлялося ростом наявності CD68-позитивних (p < 0,001) та МРО-позитивних клітин (p < 0,001). Одночасно з цим у неопластичній тканині знижуються інтенсивність процесів ангіогенезу та експресія «стресових» маркерів, що виявлялося зниженням кількості VEGF-позитивних (p < 0,05) та Hsp90-позитивних (p < 0,001) пухлинних клітин. Установлено, що за наявності простатолітів у пухлинній тканині достовірно підвищується рівень експресії остеонектину та колагену І типу. Було показано, що ці чинники зумовлюють розвиток специфічного остеобластичного імунофенотипу пухлинних клітин, що сприяє розпізнаванню кісткової тканини циркулюючими раковими клітинами як оптимального мікрооточення для розвитку кісткових метастазів, тобто розвивається явище остеотропізму пухлинних клітин. Диссертационная работа посвящена актуальной проблеме – оптимизации диагностики и оценке течения рака предстательной железы на фоне процессов биоминерализации. По результатам научного исследования установлено клинико-эпидемиологические особенности рака предстательной железы в Сумской области. Было продемонстрировано влияние простатолитов на повышение экспрессии Вах (p < 0,001) и Casp3 (p < 0,001), установлено их влияние на изменения в количественном составе воспалительного опухолевого микроокружения, что проявлялось ростом присутствия CD68-положительных (p < 0,001) и МРО-положительных клеток (p < 0,001). Одновременно с этим в неопластических тканях снижается интенсивность процессов ангиогенеза и экспрессия «стрессовых» маркеров, проявляющееся в снижении количества VEGF-положительных (p < 0,05) и Hsp90-положительных (p < 0,001) опухолевых клеток. Установлено, что при наличии простатолитов в опухолевой ткани достоверно повышается уровень экспрессии остеонектина и коллагена I типа. Было показано, что эти факторы обуславливают развитие специфического остеобластического иммунофенотипа опухолевых клеток, что способствует распознаванию костной ткани циркулирующими раковыми клетками в качестве оптимального микроокружения для развития костных метастазов, то есть развивается явление остеотропизма опухолевых клеток. The topic of thesis is devoted to the actual problem – optimization of diagnostics and evaluation of the course of prostate cancer with biomineralization. During the research the clinical and epidemiological features of prostate cancer in the Sumy region were established. The research pointed out that the presence of intraluminal inclusions in the neoplastic tissue is accompanied by its remodeling. It is manifested by cystic transformation of the glands, the development of sclerosis and periglandular inflammation, violation of the secret outflow and its stagnation. The results of the study showed the higher expression of Bax (p < 0.001) and Casp3 (p < 0.001) in the prostate cancer with prostatic calculi. It indicates the higher apoptotic potential of neoplastic cells. We also detected the increased number of CD68-positive (p < 0.001) and MPO-positive cells (p < 0.001) in the inflammatory tumor microenvironment. The massive inflammatory infiltrates were co-localized with intraluminal inclusions and were associated with mechanical traumas of tumor epithelium. At the same time the intensity of the angiogenesis and the expression of “stress» markers was lower, which was manifested in the reduction of the number of VEGF-positive (p < 0.05) and Hsp90-positive (p < 0.001) tumor cells in the prostate cancer with prostatic calculi. We also have indicated the presence of Hsp70 and Hsp90 in the corpora amylacea structure. It has been established that the levels of osteonectin and type I collagen are significantly higher in the prostate cancer with biomineralized intraluminal inclusions. The presence of intraluminal inclusions causes a change in carbohydrate composition of neoplastic tissue. We pointed out that tissue of prostate cancer with intraluminal inclusions has a lower presence of neutral carbohydrates and a higher presence of acidic glycosaminoglycan. The mineral component of prostatic calculi was represented by calcium phosphate as a calcium hydroxyapatite with admixture on another element, such as magnesium and zinc. The layered structure indicates the cyclicality of the prostatic calculi formation, involvement of both organic and inorganic components in their development. Structural study revealed a similarity of prostatic calculi structure to the unchanged bone tissue. A patent for the extraction of prostatic intraluminal inclusions from paraffin embedded prostate cancer tissue was registered. We found a fundamental difference in the mechanisms of corpora amylacea and prostatic calculi formation. The corpora amylacea are predominantly formed due to matrix growth on the intraluminal detritus, whereas the prostatic stones are formed by direct precipitation from the supersaturated solution. The combination of these factors has a modifying effect on tumor cells and predetermine the development of their specific osteoblastic phenotype. This phenomenon can contribute to the recognition of bone tissue by circulating cancer cells as an optimal microenvironment for the development of bone metastases, that is, the phenomenon of osteotropism of tumor cells develops.
Патоморфологическая характеристика биоминерализации при раке предстательной железы
Pathomorphological characterization of biomineralization in prostate cancer
Keywords: рак передміхурової залози; імуногістохімічне дослідження; простатоліти; остеобластичний імунофенотип; гідроксіапатит; остеонектин; запалення; рак предстательной железы; иммуногистохимическое исследование; простатолиты; остеобластический иммунофенотип; гидроксиапатит; воспаление; prostate cancer; immunohistochemistry; prostatic calculi; osteoblastic immunophenotype; calcium hydroxyapatite; osteonectin; inflammation